OUTCOME OF ANTEPARTUM INTRAVENOUS FERRIC CARBOXYMALTOSE IN ANEMIC PATIENTS - FAIZ , A; ASHIQ , F; KAUSAR , Z; SALEEM , L; BATOOL , S; FAROOQ , N (Biological and Clinical Sciences Research Journal, 2024)
Iron deficiency anaemia (IDA) is a prevalent condition among pregnant women, leading to increased maternal and fetal complications. Intravenous (IV) iron therapy, particularly ferric carboxymaltose (FCM), has been proposed as an effective treatment for rapid haemoglobin (Hb) improvement. Evaluating the effectiveness of FCM in achieving target Hb levels in a short duration is essential for optimising maternal health outcomes. Objective: To determine the efficacy of ferric carboxymaltose (FCM) in increasing haemoglobin levels for the treatment of iron deficiency anaemia (IDA) in pregnant women at a tertiary care hospital in Islamabad. Methods: A descriptive case series was conducted at a tertiary care hospital in Islamabad. The study included 110 pregnant women diagnosed with IDA. All participants received 5 mg of folic acid daily and were administered IV-FCM. Patients were monitored for three hours post-infusion for any adverse reactions and attended weekly follow-ups. Hemoglobin levels and iron profile were reassessed after three weeks to evaluate treatment efficacy. Data analysis was performed using SPSS version 20, with results presented as mean ± standard deviation (SD) and frequencies. Results: The mean age of participants was 25.67 ± 5.47 years (range 18–40 years). The effectiveness of IV-FCM in increasing haemoglobin levels within three weeks was observed in 80 (72.73%) of patients, indicating a high success rate. Conclusion: Ferric carboxymaltose (FCM) is effective in achieving target haemoglobin levels (≥11 g/dL) within three weeks in pregnant women with IDA, with minimal side effects. These findings support using IV-FCM as a safe and efficient treatment for iron deficiency anaemia during pregnancy.